Association of interleukin-1β gene polymorphisms in the occurrence of gastric ulcer in Southern Odisha, India - Agarwal, Suman; Naik, Aparupa; Behera, Samira Kumar; Purohit, Prasanta; Mohanty, Sudhanshu Sekhar (Rzeszów University Press, 2025)
Introduction and aim. The occurrence of gastric ulcer (GU) is influenced by many factors including interleukin 1β (IL-1β) gene polymorphisms. In this study, the association of GU with IL-1β gene polymorphisms was investigated in patients with gastric disorders. Material and methods. The patients were categorized into two groups, group 1: patients with normal impression in the upper-GI-endoscopy (n=135); group 2: patients with GU (n=135). Three single nucleotide variants (SNVs) of IL-1β gene [rs16944 (–511 C/T), rs1143627 (–31 C/T) and rs1143634 (+3954 C/T)] were investigated by PCR-RFLP method. Results. The association of IL-1β gene polymorphisms and occurrence of GU along with other factors (socio-demographic and habits) showed patients with smoking, alcohol intake and NSAID use was high in group 2. For SNVs and occurrence of GU, rs1143627 (–31 ‘TT’) genotype was significantly high in group 2 (21.48%) compared to group 1 (9.63%), while the other two genotypes were comparable. Further, there was no association of any genotypes with smoking, alcohol intake and NSAID use, except NSAID use with rs1143627 (–31 C/T) in group 1. Conclusion. The findings revealed, the habits like smoking, alcohol intake and recurrent NSAID use may influence the occurrence of GU while, the IL-1β gene polymorphisms have minimal impact on the occurrence of GU.
This study was approved by the Institutional Ethical Committee (IEC) of M.K.C.G. Medical College, Berhampur, Odisha (No. 819 /Chairman-IEC, M.K.C.G. Medical College, Berhampur-4).
Keywords: gastric ulcer; gene polymorphism; interleukin-1β; non-steroid anti-inflammatory drug